Quality comparison of indirect sun-drying and sulphur fumigation methods on copra production and storage. Issue 1 (January 2022) - Panjaitan, L; Achrom, M; Suherman, B; Nursusilawati; Fauziaty, M R; Kurniasih, K T; Wungkana, J
Abstract: As the most valuable product of coconut, copra demands good handling on its production to reduce cost in the extraction step. This work aimed to evaluate indirect sun-drying and sulphur fumigation methods to dry copra and their effects during storage. Five treatments of different dosages of sulphur fumigation (30, 35, 40, 45, and 50 gr/m 3 ), one non-fumigated indirect sun-dried treatment (NFNS), and one direct sun-dried treatment were done to observe the difference in the copra's quality. Analysis showed that sulphur fumigation and NFNS treatments did not affect physical parameters like color, hardness, and water content. Furthermore, sulphur fumigated samples were found superior to the other treatments in terms of pest and microorganism activities even after two months of storage. Generally, the sulphur and free fatty acid (FFA) contents did not exceed the allowable threshold. Interestingly, however, it was found that the fumigated copras have the lowest while the NFNS treatment shows the highest percentage of FFA contents. Therefore, this study also suggests a 50 gr/m 3 dosage of sulphur to maintain the copra quality during a longer storage time.